KAJIAN PERAN STRATEGIS PELABUHAN PERIKANAN TERHADAP PENGEMBANGAN PERIKANAN LAUT - ERNANI LUBIS (Akuatik: Jurnal Sumberdaya Perairan, 2011)
Fishing port has very important role toward the development of marine fisheries, since fishing port is the economic center from landed fish until the fish to be marketed in the port. The purpose of this study was to determine how far the strategic role of the fishing port to the development of marine fisheries and fishing industries through qualitative descriptive methods. Fishing port as a center of economic activity of fishing in Indonesia, the conditions are very limited. Currently the number of fishing ports incomparable to vast potential of fisheries and the vast marine areas especially in eastern Indonesia. The condition of existing facilities at fishing port most unfit or sub-standard so it is difficult to expect domestic and foreign investors to come invest. Undeveloped fishing port in Indonesia is also due to weak management capabilities along with weak policy support and legal instruments. The strategic role of fishing port to marine fisheries would still not optimal. It indicated, among others, are still not done with good handling of the catch in the fishing port which result in decreased quality and selling price; still not companies that invest in industrial processing because of limited facilities and poor management and availibility of raw materials that are not continoues